Paris-Amsterdam Underground Essays on Cultural Resistance, Subversion, and Diversion - Hussey, Andrew; Lindner, Christoph, 1971-; Project Muse; Project Muse. (Project Muse, 2020)
The postwar histories of Paris and Amsterdam have been significantly defined by the notion of the "underground" as both a material and metaphorical space. Examining the underground traffic between the two cities, this book interrogates the countercultural histories of Paris and Amsterdam in the mid to late-twentieth century. Shuttling between Paris and Amsterdam, as well as between postwar avant-gardism and twenty-first century global urbanism, this interdisciplinary book seeks to create a mirroring effect over the notion of the underground as a driving force in the making of the contemporary European city.
Foreword / David Pinder -- Concepts and Practices of the Underground / Christoph Lindner and Andrew Hussey -- Part 1: Projections. Metromania or the Undersides of Painting / Sophie Berrebi -- Mapping Utopia: Debord and Constant between Amsterdam and Paris / Andrew Hussey -- Amsterdam's Sexual Underground in the 1960s / Gert Hekma -- Part 2: Mobility. Detours, Delays, Derailments: La Petite Jerusalem and Slow Training in Culture / Sudeep Dasgupta -- Underground Visions: Strategies of Resistance along the Amsterdam Metro Lines / Ginette Verstraete -- Underground Circulation: The Beats in Paris and Beyond / Allen Hibbard -- Part 3: Visibility. (In)audible Frequencies: Sounding out the Contemporary Branded City / Carolyn Birdsall -- Red Lights and Legitimate Trade: Paying for Sex in the Branded City / Joyce Goggin -- Visibly Underground: When Clandestine Workers Take the Law into Their Own Hands / Anna-Louise Milne -- Archaeology of the Parisian Underground / Stephen W. Sawyer.
Issued as part of book collections on Project MUSE.
Includes bibliographical references (pages 171-182) and index.
Description based on print version record.
Keywords: Counterculture -- France -- Paris; Counterculture -- Netherlands -- Amsterdam; Electronic books; Electronic books